Home Automation Management with WLAN (802.11g) and RF Remote Control - Mahmood Majeed; Abdulsattar Khidhir; Firas Yosif (Al-Rafidain Journal of Computer Sciences and Mathematics)
The home automation becomes important, because it gives the user the comfort and ease for using the home devices. The implementation and design of wireless home automation control use two methods, WLAN technology and RF remote control handheld to control selective home devices with integral security and protected system. The devices have been distributed in two rooms, each room has own board, these boards are connected to the desktop personal computer (PC) through one serial port RS-232 via microcontroller. The software consists of Assembly Language for programming microcontroller (AT89C51and AT89C2051) and Visual Basic Language that use to communicate between PC and two boards, also it use to design Graphical User Interface (GUI) which involving all devices needed to display in Home PC screen .  The system is low cost and flexible with the increasing variety of devices to be controlled.